PENGARUH KOMPETENSI, MORAL KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI - Idris, Sartika; Basyir, Muhammad (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
Abstrack:This study aims to determine the effect of competence work morale and motivation on employee performance. This study was conducted at SETDA District staff. Gayo Lues uses a questionnaire as a research instrument, where the sample in this study is 100 respondents. Probability Sampling Technique is used as a sampling technique using the total sampling method. Multiple linear analysis method is used as a method of data analysis using IBM SPSS 23. Data collection techniques used are questionnaires. The instrument for this research instrument is validity and reliability testing. While for hypothesis testing using the t test. In this study the researchers also used multiple linear regression analysis to analyze the data and strengthened with the classic assumption test, namely the normality test, multicollinearity test and heterocedasticity test. The results of this study indicate that the Competency variable does not significantly influence employee performance, Job Moral has a significant effect on employee performance , and work motivation has a significant effect on Employee Performance with results of R0.515 (51.5%). These results indicate that the variables included in this study are only 51.5% in other words there are still 48.5% of other variables that have not been included in this study. For further researchers, it is expected to include other variables not found in this study so that they can obtain maximum results.